2014
DOI: 10.1590/0047-2085000000041
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças nos aspectos cognitivos entre idosos praticantes e não praticantes de exercício físico

Abstract: Objetivo Comparar o desempenho cognitivo de idosos praticantes e não praticantes de exercícios físicos. Métodos Este estudo transversal foi realizado com 104 idosos, sendo 64 pertencentes ao Grupo Praticantes de exercícios físicos (G1) e 40 pertencentes ao Grupo não Praticantes (G2), cadastrados em Centros de Saúde. Foram aplicados o Miniexame de Estado Mental (MEEM) para avaliar o estado cognitivo e uma ficha para caracterização da amostra. Posteriormente, aplicou-se a Bateria de Avaliação Cognitiva Compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
0
7
0
14
Order By: Relevance
“…No studies were found which evaluated such cognitive characteristics specifically, with the assessment of cognitive function solely through utilization of cognitive tests to evaluate skills being common in literature. 4,6 For Borges et al, 31 elderly persons living in LTCFEs become increasingly sedentary and lose much of their autonomy which, allied to the aging process, can enhance cognitive decline. However, the study by Carneiro et al, 16 performed with 59 elderly residents in two LTCFEs in the city of Fortaleza, Ceará, demonstrated that the elderly showed independence in carrying out their daily activities (food, personal hygiene, bathing, mobility and sphincter control), needing help just with movement on stairs and with small defects in memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No studies were found which evaluated such cognitive characteristics specifically, with the assessment of cognitive function solely through utilization of cognitive tests to evaluate skills being common in literature. 4,6 For Borges et al, 31 elderly persons living in LTCFEs become increasingly sedentary and lose much of their autonomy which, allied to the aging process, can enhance cognitive decline. However, the study by Carneiro et al, 16 performed with 59 elderly residents in two LTCFEs in the city of Fortaleza, Ceará, demonstrated that the elderly showed independence in carrying out their daily activities (food, personal hygiene, bathing, mobility and sphincter control), needing help just with movement on stairs and with small defects in memory.…”
Section: Discussionmentioning
confidence: 99%
“…2 Levels of cognitive disorder increase as a population ages, meaning that there is a current global rise in the same, constituting a major mental health problem. 3 In this sense several studies [4][5][6] have highlighted the relationship between aging and the onset of cognitive disorders (dementia, reaction time, memory deficit, understanding and learning), also describing how such disorders can be influenced by factors such as age, education, physical activity and income. 4,6 The assessment of cognitive ability has arisen, therefore, as a new health paradigm, of particular importance for the elderly, originating from the concept of health and quality of life, combined with increased life expectancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, neste estudo quase a totalidade das idosas não apresentaram déficit cognitivo, aspecto este que parece estar relacionado à participação no grupo de idosos e à realização das atividades cognitivas, recreativas e físicas que são praticadas, como as realizadas no Cati -São José/ SC (RIBEIRO; NERI, 2012;CASAGRANDE;CARPES, 2013;FIGUEIREDO et al, 2013;DIAS et al, 2014).…”
Section: Discussionunclassified
“…Os declínios cognitivos podem acarretar modificações físicas, sociais e emocionais, bem como prejuízos da memória, podendo este ocasionar desde pequenos esquecimentos até severos comprometimentos 3 . Assim, alterações cognitivas podem comprometer a qualidade de vida dos idosos em vários aspectos funcionais e predispõe ao surgimento de diversas patologias, como a doença de Alzheimer que reflete diretamente na memória 4 . A memória exerce importante influência sobre a autonomia e independência na vida cotidiana, destacando que 50% dos idosos apresentam queixas frequentes de memória 5 .…”
Section: Introductionunclassified